The Effect of E-Service Quality and E-Trust on E-Loyalty Through E-Satisfaction for Codashop Game Top Up Shop Customers - Kasfunnuri, M. Asren; Hermawan, Agus; Dewi, Titis Shinta (Journal of Applied Business, Taxation and Economics Research, 2025)
Gaming is an industry that is greatly affected by technological advances. The number of online game players causes the game top up site to grow. This study aims to examine the effect of e-service quality and e-trust on e-loyalty through e-satisfaction in Codashop customers. This study uses the Unified theory of acceptance and use of technology (UTAUT). This research is quantitative research using descriptive and explanatory analysis. The sampling method in this study was a nonprobability sampling method with purposive sampling technique. The number of samples in this study were 267 respondents. The analysis technique in this study is descriptive statistical analysis and inferential analysis (PLS) using SmartPLS 4.0 software. The results of this study indicate that e-service quality has a positive and significant effect on e-loyalty. E-trust has a positive and significant effect on e-loyalty. E-satisfaction has a positive and significant effect on e-loyalty. e-service quality has a positive and significant effect on e-satisfaction. E-trust has a positive and significant effect on e-satisfaction. E-service quality has a positive and significant effect on e-loyalty through e-satisfaction. E-trust has a positive and significant effect on e-loyalty through e-satisfaction